The Effect of Using Word Flipchart Media on Reading Ability in Group A Students in Kindergarten: Pengaruh Penggunaan Media Flipchart Kata Terhadap Kemampuan Membaca Pada Siswa Kelompok A di Taman Kanak - Diana Chuzza; Choirun Nisak Aulina (Academia Open, 2022)
The purpose of this study was to analyze the influence of word flipchart media on the reading ability of group A children at Dharma Wanita Persatuan Tlasih Kindergarten, Tulangan District. This study uses a quantitative method of pre-experiment type one-group pretest-posttest design. The population of this research is the children of group A TK Dharma Wanita Persatuan Tlasih, Tulangan District with saturated sampling technique with 16 students. The data collection technique in this study used the results of the initial reading ability test. The data analysis technique used the dependent t test with the research results tcount = 11.30 and ttable = 2.131 so that tcount > ttable, then H1 was accepted and H0 was rejected. This shows that there is an effect of word flipchart media on the reading ability of group A children at Dharma Wanita Persatuan Tlasih Kindergarten, Tulangan District. Keywords: Word Flipchart Media, Reading Ability.